THE RELATIONSHIP BETWEEN DEMENTIA AND PHYSICAL ACTIVITY: A SYSTEMATIC REVIEW - Donka, Dorottya Bianka; Balogh, László (Stadium - Hungarian Journal of Sport Sciences, 2020)
Introduction: Many studies have already shown that, there is connection between physical actitity and cognitive functions. Therefore, the aim of our research is to examine the relationship between cognitive decline (dementia) and physical activity.Method: The research genre was a secondary method analysis. The literature review was primarily collected from articles published on international scientific sites.Results: A total of 11 reviews were examined, examining the relationship between dementia and physical activity, which included 217 articles. Research has supported our hypothesis, that regular exercise has a positive effect on the prevention of dementia by reducing the risk of dementia.Conclusion: It would be worthwhile to further investigate, which types of exercise at what repetition rate and what intensity achieve the best results in reducing the risk of dementia, or slowing the process of dementia.